Survey on Scheduling Algorithms in Cloud Computing - Sathya Sofia, A.; Backialakshmi, M. (Asian Journal of Electrical Sciences, 2014)
Cloud computing is a general term used to describe a new class of network based computing that takes place over the internet. The primary benefit of moving to Clouds is application scalability. Cloud computing is very beneficial for the application which are sharing their resources on different nodes. Scheduling the task is quite a challenging in cloud environment. Usually tasks are scheduled by user requirements. New scheduling strategies need to be proposed to overcome the problems proposed by network properties between user and resources. New scheduling strategies may use some of the conventional scheduling concepts to merge them together with some network aware strategies to provide solutions for better and more efficient job scheduling. Scheduling strategy is the key technology in cloud computing. This paper provides the survey on scheduling algorithms. There working with respect to the resource sharing. We systemize the scheduling problem in cloud computing, and present a cloud scheduling hierarchy.